WAWASAN AL-QUR`AN DALAM MODERASI BERAGAMA: PERKEMBANGAN PARADIGMA - Syafi’i, Imam; Nugroho, Irzak Yuliardy (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2021)
This study examines the development of the Qur'anic Study Paradigm, by knowing this development, one has a broad view and avoids radical and extreme attitudes. In addition, an anti-violence attitude in responding to differences, contextualization in understanding religious texts. This study uses a qualitative approach with the type of research library research, where researchers utilize various sources both primary and secondary contained in various journals, books and research results. Furthermore, data analysis was carried out. The development of interpretation from classical to contemporary cannot be separated from the historical roots where the Qur'an was understood by the early generations of Islam. In the classical era there were at least two stages in the study of the Qur'an, namely formative with Quasi-Critical reasoning or paradigms and affirmative with ideological reasoning. Post-Orientalism, criticism of the Qur'an became a prominent theme in the West. This phase is called transformative. This stage is called the reformative era with critical reasoning. Existing interpretation products are not taken for granted as 'truth'. However, they have begun to be criticized and questioned, while transformative means that interpretation is built to transform the people and to answer and solve real problems that are emerging and developing in society.Â